2007
DOI: 10.1177/1056492607305894
|View full text |Cite
|
Sign up to set email alerts
|

Are Articles in “Top” Management Journals Necessarily of Higher Quality?

Abstract: This study investigates the appropriateness of using publication of an article in a top (specifically, top five) management journal as a proxy for its quality. Social Science Citation Index citation counts were collected over 7-year event windows for articles published in 34 management journals in 1993 and 1996. Overall, the authors found that articles published in the five journals most often considered to be the top ones in management tend to be cited more often than ones published in the other journals. Far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 33 publications
2
88
0
1
Order By: Relevance
“…Many studies have established that highly-cited articles get published in journals that are not considered top journals in the field, and a substantial proportion of the articles published in top journals fail to generate a high level of citations (cf. Starbuck, 2005, Oswald, 2007and Singh, Haddad & Chow, 2007. Hence using journal proxies to evaluate the impact of individual articles can lead to substantial attribution errors.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have established that highly-cited articles get published in journals that are not considered top journals in the field, and a substantial proportion of the articles published in top journals fail to generate a high level of citations (cf. Starbuck, 2005, Oswald, 2007and Singh, Haddad & Chow, 2007. Hence using journal proxies to evaluate the impact of individual articles can lead to substantial attribution errors.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, o uso de tal fórmula de avaliação como o principal indicador de desempenho de pesquisa acadêmica e de qualidade é arruinado por dificuldades, particularmente ao se incentivar fortemente a pesquisa incremental. Há também uma fraca relação entre os estudos influentes no sentido do impacto da citação e onde eles são publicados (ADLER, 2009;GLICKET et al, 2007;PFEFFER, 2007;SINGH et al, 2007). Pfeffer (2007Pfeffer ( , p. 1342) observou que investigação sobre contagens de citações "ilustra que uma proporção chocantemente alta de artigos, mesmo aqueles publicados em revistas renomadas, acumula zero citação, e uma porcentagem ainda maior obtendo muito poucas".…”
Section: Governosunclassified
“…Singh, Haddad, and Chow found that top management journals received more citations, but that not all the articles in top journals were of the same quality. 40 In a study related to journal lists, Bornmann and Dieter found that citation decisions are a complex phenomenon that includes both social and practical aspects. 41 Other critiques of journal lists from business fields focus on the use of those lists by departments or colleges.…”
Section: Business Core Journal Lists: Critiquesmentioning
confidence: 99%
“…56 Being familiar with the literature that critiques journal ranking may provide the evidence departments need to change their evaluation methods. Research that explores individually evaluating articles for merit has been done by Mingers, Watson, and Scaparra.…”
Section: Implications For Librariansmentioning
confidence: 99%